Causal relationships between height, screen time, physical activity, sleep and myopia: univariable and multivariable Mendelian randomization - Liu, Xiaoyu; Zhao, Fangkun; Yuan, Weichen; Xu, Jun (Frontiers in Public Health, 2024)
Background This study aims to investigate the independent causal relation between height, screen time, physical activity, sleep and myopia. Methods Instrumental variables (IVs) for exposures and outcome were obtained from the largest publicly available genome-wide association studies (GWAS) databases. First, we performed a bidirectional univariate MR analysis using primarily the inverse variance weighted method (IVW) with height, screen time, physical activity and sleep as the exposure and myopia as the outcome to investigate the causal relationship between exposures and myopia. Sensitivity analysis was used to demonstrate its robustness. Then the multivariable MR (MVMR) and MR-based mediation approach was further used to estimate the mediating effect of potential confounders (education and time outdoors) on causality. Results The results of univariate MR analysis showed that taller height (OR = 1.009, 95% CI = 1.005–1.012, p = 3.71 × 10−7), longer time on computer (OR = 1.048, 95% CI = 1.029–1.047, p = 3.87 × 10−7) and less moderate physical activity (OR = 0.976, 95% CI = 0.96–0.991 p = 2.37 × 10−3) had a total effect on the increased risk of developing myopia. Meanwhile our results did not have sufficient evidence to support the causal relationship between chronotype (p = 0.637), sleep duration (p = 0.952) and myopia. After adjusting for education, only taller height remains an independent risk factor for myopia. After adjusting for education, the causal relationship between height, screen and myopia still had statistical significance. A reverse causal relationship was not found in our study. Most of the sensitivity analyses showed consistent results with those of the IVW method. Conclusion Our MR study revealed that genetically predicted taller height, longer time on computer, less moderate physical activity increased the risk of myopia. After full adjustment for confounders, only height remained independently associated with myopia. As a complement to observational studies, the results of our analysis provide strong evidence for the improvement of myopia risk factors and provide a theoretical basis for future measures to prevent and control myopia in adolescents.